MANAJEMEN PEMASARAN STRATEGIS PENDIDIKAN: MENINGKATKAN CITRA LEMBAGA MELALUI PRAKTIK INOVATIF - Moh. Rofiki; Susmiati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Improving a school's image is an important strategy for reducing competition in education. This research analyzes marketing management and innovation in education marketing in schools in improving positive image. A qualitative approach with a case study type was used in the research. Data were collected using participant observation, in-depth interviews, and documentation studies. Data analysis consisted of data reduction, data display, and conclusion drawing. The results of the study of SDN Karangegar 1, a school that has successfully run innovative programs including partnering with English language course institutions and bringing in Caucasians, partnering with regional libraries and bringing in mobile libraries once a month, and collaborating with community health centers. In addition, this strategy is not only the best way to achieve the highest qualification, but also the school's reputation as an innovative and responsive institution to the community has increased. These insights can serve as a reference for other institutions that want to enhance their appeal and reputation by improving the image of the institution.